NILAI SASTRA ANAK DALAM CERITA RAKYAT KALIMANTAN BARAT SEBAGAI SARANA PENDIDIKAN KARAKTER - Oktavia, Bintari; Effendy, Chairil; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrack Abstract: aim of this study is to obtain data and description about personal and education value in Melayu AH fairy tale and SBPR folklore. This study using descriptive, qualitative, and objective approach method. Based on analysis of data, it can be concluded that in the collection Melayu AH and SBPR folklore, can be found. 1) Personal value in Melayu AH dan SBPR folklore are analysis on emotional gain, including expression of anger, fear, sadness, and happiness that shown by attitude and behavior. On intellectual gain, found learning about causes and effects of problems that commonly found in daily life. On imagination gain, found imaginative views which can stimulate creativity of children. On social gain, found many interaction between people and community, except in SBPR, not found social meaning. On ethical and religious, found learning about assessment of human behavior quality and belief in God. 2) Education value in Melayu AH dan SBPR folklore including analysis on exploration and inventory. Found many inventions such as origin of living things, except in SRMSRB, not found exploration and inventory. On language gain, found Malay uses, except in SBPR, the language that used is Dayak. On beauty value, found the meaning of beauty, included by sentence structure. On multicultural views, found thing which can add children views about the culture of a region, except in SRMSRB and SBPR, the thing was not found.  Keywords : value, children?s literature, folklore